Introduction to Three Lycée Essays by Gramsci - Righi, Maria Luisa (International Gramsci Journal, 2024)
This article introduces the three newly discovered essays written by Gramsci while still at the Dettori high school in Cagliari and goes into why they have only recently come to light, to then be published in 2022 in the Italian newspaper “Il fatto quotidiano”. The essays turned up in the family papers of a Communist Party parliamentarian from Milan, Francesco Scotti, a Spanish Civil War veteran and after that a partisan leader (in the French Maquis and then in Italy) among whose friends in Milan were prople associated with Gramscian activities, among them Carlo Gramsci, the younger brother of Antonio. It seems likely that Scotti was given these essays by someone in this group to hand them over to the PCI in Rome, probably to Togliatti, but neglected to do this and so they remained forgotten for years. The essays themselves can with certainty be dated to Gramsci’s last year at the high school since the signature of the professore is Vittorio Amedeo Arullani, who had replaced Raffa Garzia as Gramsci’s Italian teacher. The essay subjects assigned were quotations from the sixteenth century writer Giovanni Della Casa’s treatise Il Galateo (in recent English versions The Rules of Polite Behavior) and two of Italy’s most important poets, Giacomo Leopardi and Giosuè Carducci. For all these essays by Gramsci, Arullani gave positive judgments and very high grades. One sees a student very open to the contemporary currents of thought, whose essays prefigure themes that later come explicitly to the fore both in his journalistic work and in the Prison Notebooks (artistic currents and aesthetics, Americanism, the “mummification” of culture, the figure of Stenterello, Kant’s “beheading” of God, Jesuitism and so on).